The Effect of Appendicular Peritonitis on the Reproductive Function of Girls - Yusupov, M.Shukhrat Abdurasulovich; Davranov, Bobir Latibovich; Makhmatkulov, Khomidullo Gaybullaevich (RA Journal of Applied Research, 2022)
After surgery for gangrenous - perforated appendicitis, miscarriage occurs in 11%, infertility in 62% of cases. The aim of the study was to develop an algorithm for the diagnosis and treatment of reproductive dysfunction in women who underwent common appendicular peritonitis in childhood. 154 girls aged 3 to 15 years were examined. The results showed that various pathologies from the reproductive system (ovarian failure, inflammatory processes, tubal peritoneal infertility) were diagnosed in 47 (30,5%) patients, while more than half of them 28 (59,6%) did not show any complaints and pathology was identified during the examination. The developed algorithm allows for timely diagnosis and treatment of complications of reproductive function in girls after suffering from diffuse appendicular peritonitis.